'Reflexive modernity' and the transition experiences of university athletes. (October 2013) - Falls, Dominique; Wilson, Brian
Although there is a tradition of research focused on the socialization experiences of student-athletes, few studies consider how non-sport-related transitions impact and overlap with the sport-related transitions experienced by these athletes – or how transition experiences are influenced by the broader, structural conditions associated with reflexive modernity. With the goal of addressing these gaps, an interview-based study of the experiences of 12 female student-athletes, who moved from Canada to the United States to pursue intercollegiate soccer, is reported. The study is situated in literatures related to youth transitions, mobility, sport-related socialization, and identity formation. The 'individualization' and 'detraditionalization' concepts are featured and considered for their pertinence to the experiences of the interviewed student-athletes. Key findings from the study include the following: decision-making by student-athletes was a predominantly individualized endeavor that was influenced by various sport and non-sport-related factors; the sport and non-sport-related transitions that accompanied the move to a new sporting and educational context were eased because of the (temporary and conditional) support of teammates; and that the transition out of sport was especially difficult for many of the athletes, as the support structures associated with 'the team' quickly diminished – and because of the hyper-individualized identities that the student-athletes were required to renegotiate.